KAJIAN TEOLOGIS TERHADAP SPIRITUALITAS BUMI MENURUT PERSPEKTIF KRISTEN - Duapadang, Enry Yakobus; Fransiska, Ni Nyoman (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2023)
Earth is a creation of God and is considered a holy place filled with God's presence. However, along with the development of the times and the human tendency to increasingly dominate nature, the Earth is often seen as only an object that can only be utilized. In this theological view, earth spirituality is seen as a human relationship with the Earth that shows respect, togetherness, and interdependence. Earth spirituality teaches that humans and Earth are connected and influence one another. In the context of Christian theology, earth spirituality emphasizes the importance of protecting and caring for God's creation as a form of responsibility and respect for the Creator. In a practical context, earth spirituality can be applied to human daily life through practices that are environmentally friendly and promote natural sustainability. Churches and Christian communities can play an important role in promoting environmental awareness and practices. In a theological view, protecting the environment is a form of service to God and others. In its conclusion, the Christian theological view of earth spirituality emphasizes the importance of understanding humanity's relationship with the Earth from a theological perspective. Earth spirituality views Earth as a sacred place that must be respected and cared for. In a practical context, earth spirituality can be applied to human daily life through environmentally friendly practices.